CD8+ cytotoxic T lymphocytes in cancer immunotherapy: A review - Farhood, Bagher; Najafi, Masoud; Mortezaee, Keywan (Journal of cellular physiology, 2019)
CD8+ cytotoxic T lymphocytes (CTLs) are preferred immune cells for targeting cancer. During cancer progression, CTLs encounter dysfunction and exhaustion due to immunerelated tolerance and immunosuppression within the tumor microenvironment (TME), with all favor adaptive immune‐resistance. Cancer‐associated fibroblasts (CAFs), macrophage type 2 (M2) cells, and regulatory T cells (Tregs) could make immunologic barriers against CD8 + T cell‐mediated antitumor immune responses. Thus, CD8 + T cells are needed to be primed and activated toward effector CTLs in a process called tumor immunity cycle for making durable and efficient antitumor immune responses. The CD8 + T cell priming is directed essentially as a corroboration work between cells of innate immunity including dendritic cells (DCs) and natural killer (NK) cells with CD4 + T cells in adoptive immunity. Upon activation, effector CTLs infiltrate to the core or invading site of the tumor (so‐called infiltrated–inflamed [I–I] TME) and take essential roles for killing cancer cells. Exogenous reactivation and/or priming of CD8 + T cells can be possible using rational immunotherapy strategies. The increase of the ratio for costimulatory to coinhibitory mediators using immune checkpoint blockade (ICB) approach. Programmed death‐1 receptor (PD‐1)–ligand (PD‐L1) and CTL‐associated antigen 4 (CTLA‐4) are checkpoint receptors that can be targeted for relieving exhaustion of CD8 + T cells and renewing their priming, respectively, and thereby eliminating antigen‐expressing cancer cells. Due to a diverse relation between CTLs with Tregs, the Treg activity could be dampened for increasing the number and rescuing the functional potential of CTLs to induce immunosensitivity of cancer cells. Tumors have specific mechanisms to break T cell responses. CD8+ T cells are the key immune cells for killing cancer cells presenting major histocompatibility complex (MHC) class I molecules. For pursuing this purpose, the cells must first be primed by their cardinal interactions with dendritic cells (DCs), natural killer (NK) cells, and CD4 + T cells, among them play essential roles for this priming. Then, the primed cells are activated to form effector cytotoxic T lymphocytes (CTLs) for killing cancer cells via release of granules or induction of FasL‐mediated apoptosis. In the established tumors, however, the function of these key effector cells is suppressed by immunosuppressive cross‐talking between cancer cells with tumor stromal cells like cancer‐associated fibroblasts (CAFs), regulatory T cells (Tregs), and macrophage type 2 (M2) cells. CTL‐based therapy can distract cancer cells, and the density of CD8 + T cells infiltrated to the invasive site of tumor is a predictive marker for influencing the outcomes of immune checkpoint blockade (ICB) blockade therapy. It is suggested to use a combination of immunotherapeutic approaches for rescuing the exhausted CTLs and switching them toward their active effector profile for retaining immunoactivation within the tumor microenvironment (TME) for combatting tumors and enhancing the efficacy of chemo or radiotherapeutic approaches.